Evaluation Of Governance Of Local Goverment Information System In Ministry Of Home Affairs Of The Republic Of Indonesia - Rabin Ridho Dinata; Mansyur Achmad; Dedeh Maryani; Ika Sartika (Jurnal Syntax Transformation, 2025)
Some obstacles faced by several OPDs, due to the large number of menus that must be filled in the input in SIPD, employees often miss one of the input processes so that the resulting report is different, delayed budget shifts, hampered payroll systems, and also the SIPD network which often errors so that there are obstacles in the preparation of cash budgets, making SPD, SPJ, SPP, SPM and making SP2D. Of the 105 menus available, there are 14,661 problems reported by the local government, of which 9,960 reports can be resolved while 4,701 problems are still in the process of being resolved. The purpose of this research is to identify, analyze and understand the governance of regional government information systems at the Ministry of Home Affairs, as well as to design an ideal model for governance of regional government information systems at the Ministry of Home Affairs. This study uses the theory of policy evaluation proposed by Dunn (2000:610). The research method used is qualitative research with a descriptive approach. Data collection techniques are carried out by interview, observation and documentation. The results of the study indicate that the Regional Government Information System policy is not optimal due to: There is no Steering Committee specifically assigned to supervise and manage development and implementation. The absence of a special committee causes a lack of cross-echelon coordination in strategic decision-making related to SIPD development. Many technical and policy constraints related to SIPD that require cross-directorate decision-making are not resolved quickly, resulting in delays in implementation. There is no formal mechanism for monitoring, evaluating, and following up on policies that are integrated into one leadership structure. The appropriate model for optimizing the Regional Government Information System Policy is called the SIPD Governance Model. This model refers to 4 (six) SIPD governance, namely: SIPD service catalog, Service management organization, Definition of Level and SIPD Service Operational Support System.